2015
DOI: 10.1074/jbc.m115.657023
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Heat Shock Protein 90 (Hsp90)-Protein Kinase Cδ (PKCδ) Interaction by (−)-Maackiain Suppresses Histamine H1 Receptor Gene Transcription in HeLa Cells

Abstract: Background:The molecular mechanism of anti-allergic (Ϫ)-maackiain remains unknown. Results: (Ϫ)-Maackiain and Hsp90 inhibitors inhibited PKC␦ activation and suppressed H1R gene expression. Conclusion: (Ϫ)-Maackiain is a novel Hsp90 pathway inhibitor, and its anti-allergic activity underlies the disruption of Hsp90-PKC␦ interaction. Significance: Hsp90 is involved in H1R gene up-regulation, and its inhibition could be a novel therapeutic strategy for allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Maackiain (MK, Figure 1 ) has been isolated from the dried roots of Sophora flavescens Aiton. and has been reported to have multiple pharmacologic properties, such as the inhibitory activity on monoamine oxidase B [ 27 ] and anti-allergic [ 28 ], anti-cancer [ 29 ], and anti-inflammatory activities [ 30 ]. However, the effectiveness of MK against PD has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Maackiain (MK, Figure 1 ) has been isolated from the dried roots of Sophora flavescens Aiton. and has been reported to have multiple pharmacologic properties, such as the inhibitory activity on monoamine oxidase B [ 27 ] and anti-allergic [ 28 ], anti-cancer [ 29 ], and anti-inflammatory activities [ 30 ]. However, the effectiveness of MK against PD has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that heat shock protein 90 (Hsp90) regulated PKCδ signaling in HeLa cells (24). Therefore, we investigated the effect of quercetin and Hsp90 inhibitors on PMA-induced glucagon secretion.…”
Section: Effect Of Quercetin On Glucagon Secretion From Isolated Isletsmentioning
confidence: 99%
“…To investigate whether Y‐632 inhibited Hsp90 ATPase activity, we undertook a malachite green assay using recombinant full‐length yeast Hsp90. Considering the IC 50 values of Hsp90 inhibitors for Hsp90 ATPase activity are reported to be much higher than the concentrations that could induce degradation of Hsp90 client proteins in tumor cells, the concentration of Y‐632 we used in this assay was up to 500 μM. As shown in Figure (a), GA significantly abolished Hsp90 ATPase activity by 49% ( P < 0.05) and 95% ( P < 0.001) at 1 μM and 100 μM, respectively, but Y‐632 had no significant effect on Hsp90 ATPase activity.…”
Section: Resultsmentioning
confidence: 99%